The joyful Christian : 127 readings - Lewis, C. S. (Clive Staples), 1898-1963. (New York : Macmillan Publishing Company, 1977)
According to C.S. Lewis, "joy is the serious business of heaven," and attaining that joy is the business of the Christian. Lewis reveals his own approach to Christianity and faith in the devotional readings of The Joyful Christian. Ranging from the intrinsically spiritual -- the understanding of the nature of prayer, good works, or the incarnation -- to the very worldly -- the truth about fascism, psychoanalysis, or morality, The Joyful Christian offers inspiration to everyone who hungers and thirsts after joy. - Back cover.
Right and wrong -- The universe -- Life on other planets -- God in outer space -- Atheism -- Seeing and believing -- Miracle and the laws of nature -- Morality -- The tao -- Illustrations of the tao -- Joy -- Theology -- Divine omnipotence -- Divine goodness -- Begetting and making -- Spirit, spirits, spiritual -- The three-personal God -- The Trinity -- The fall of man -- The incarnation -- The virgin birth -- Miracles of fertility -- Miracles of healing -- Miracles of destruction -- Miracle of the resurrection -- Miracle of the walking on the water -- Miracle of the raising of Lazarus -- Miracle of the transfiguration -- Miracle of the ascension -- On seeing a miracle -- The second coming -- What are we to make of Jesus Christ? -- Putting on Christ -- Perfection -- First fervor -- Scruples -- Liturgy -- Holy communion -- Devotions to saints -- Church music -- Ready-made prayers -- Festooning ready-made prayers -- When and where to pray --
Includes bibliographical references (pages 229-235).
Keywords: Church of England; Theology; Christian life -- Anglican authors